2001
DOI: 10.1210/endo.142.12.8548
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Id2 Gene Expression by the Type 1 IGF Receptor and the Insulin Receptor Substrate-1

Abstract: The Id family of helix-loop-helix proteins is known to be involved in the proliferation and differentiation of several types of cells. The type 1 IGF receptor (IGF-IR) induces either proliferation or differentiation in 32D cells, a murine hemopoietic cell line, depending on the availability of the appropriate substrates for the receptor. We have previously reported that the IGF-IR regulates the expression of the Id2 gene in 32D cells. We now show that the IGF-IR controls the increase in Id2 gene expression thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In 32D IGF-IR cells, ID2 gene expression is very low, almost undetectable. Ectopic expression of IRS-1 in these cells causes a dramatic increase in ID2 gene expression (2,40,47; this study). Neither UBF1 nor PES1 is capable of inducing ID2 expression in 32D IGF-IR cells.…”
Section: Discussionmentioning
confidence: 54%
“…In 32D IGF-IR cells, ID2 gene expression is very low, almost undetectable. Ectopic expression of IRS-1 in these cells causes a dramatic increase in ID2 gene expression (2,40,47; this study). Neither UBF1 nor PES1 is capable of inducing ID2 expression in 32D IGF-IR cells.…”
Section: Discussionmentioning
confidence: 54%
“…The fact that the ␦PTB mutant does not translocate in response to IGF-I stimulation is not surprising because this mutant is not completely inactive but is strongly impaired in its function (23,27). It indirectly confirms, however, that the wild type IRS-1 found in the nucleus is really IRS-1, because the same antibody was used as for the wild type IRS-1.…”
Section: Discussionmentioning
confidence: 83%
“…32D IRS-1/IGF-IR cells express both the human wild type IGF-IR and mouse IRS-1 (7), are IL-3 independent, and form tumors in nude mice (11). 32D IGF-IR cells expressing the mutant IRS-1 proteins have been described previously (22,23). They are 32D IGF-IR cells stably transfected with plasmids expressing mutant IRS-1 proteins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies by Navarro et al (2001) have suggested that IGF causes upregulation of Id2; therefore in our model, Id3 may be increased as a consequence of increased IGF-II expression as a mechanism of controlling the rate of differentiation in a feed-forward loop. In addition, utilising the non-differentiating myoblast cell line NFB4, Sarbassov et al has shown that myogenin and IGF-II are capable of activating each other's expression.…”
Section: Discussionmentioning
confidence: 88%